Dinamika Gerakan Etnonasionalisme Kurdi Irak (Studi Kajian Periode 1979-2012) - Tunggul Ganggas Danisworo; Tri Cahyo Utomo; Puji Astuti (Journal of Politic and Government Studies, 2013)
The Kurds are one of the ethnic groups living in several countries in the Middle East,they have goals and ambitions of creating an independent Kurdish state and sovereignity. Butafter the first world war ended, they had to live apart due to the Kurdistan region is divided intoseveral sovereign countries (Iran, Iraq, Syria and Turkey) by the United Nations. Kurds in Iraqin the Kurdish history is the most aggressive in expressing their aspirations than the Kurds inother countries. They created an ethnic nationalist movement used in order to demand thefreedom of Kurdish aspirations. Started in 1919, Mahmud Barzanji declare the Kurdish strugglein Iraq through the uprising known as Sulaymaniyah revolution. No accommodation of theinterests of the Iraqi Kurds by successive regimes dominate Iraq, making Iraq's Kurdish ethnicrebellion continued until the end of Iraq controlled by the authoritarian regime of SaddamHussein. The period of Saddam Hussein's regime was the toughest period in the history of ethnicKurds. Various Iraqi Kurdish policy of ethnic cleansing began intensified by the authoritarianregime of Saddam Hussein, but when it is also movement in Iraq's Kurdish ethnic nationalismgrew stronger.This study describes how the patterns of strategy ethnonationalism Kurdish movement inIraq during the reign of Saddam Hussein to go into Iraq's democratic process (period 1979-2012), as well as explaining what policies have been issued in order to accommodate theinterests of Kurds in Iraq during that period. This study also describes contemporary conflictsinvolving Iraq's ethnic Kurds as an actor in the conflict. So in this research will be able to seehow it changes shape patterns of Iraqi Kurdish nationalist movement from time to time as well asthe influence behind the change.Keywords: Iraq, Kurdish, Ethnonationalism